A study on the visual effects in the movie Avengers: Age of Ultron / Nawal Mohamed A. Mohamed - Nawal Mohamed, A. Mohamed (2016)
Early of the twenty-first century, world population used to watch or to listen to different types of Hollywood media based on movies. Movies, is categorized as one of the most outstanding cultural activities. On a variety of economic and cultural phenomena in societies, nowadays, cinematic technology has added a valuable importance to the apparent sensitivity of the moviegoer‟s experience. Technologies in the contemporary period are creating digital cinematic films and produces how modern people perceive executives no longer real scenes before the camera starts recording objectively. However, they can be built by notable increases in computer generated imaging (CGI), motion capture technology and 3D digital camera systems. As the starting point of the film, audiences and producers claim a current relationship between reality and the green screen technology. Digital cinema currently allows the viewer to inhabit and interact with cinematic reality in a unique way, and this new paradigm shift from analog to digital has created the basis for new ways of watch the film and manipulated picture filmed reality. The goal of this study is to analyze the film Avengers: Age of Ultron according to its visual elements, generic elements and production and to identify the using of visual effects in a film. This research focuses on collecting information from secondary data. Secondary data sources are involved, through the analysis of qualitative methods. This study will be able to afford to show evidence that the presence of film-based manufacturer incentives such movies. However, demand for digital effects, 3D visualization, computer graphics and all other modern technologies is growing and is still steadily since its first appearanc